Digital Guillotines :Symbolism and Posthuman Disintegration in Mohsin Hamid’s Exit West - Sakar, Assistant Lecturer Khalid Salman (Thi Qar Arts Journal, 2025)
This paper examines Mohsin Hamid’s Exit West through the dual theoretical lens of literary symbolism and posthumanist philosophy. It argues that the novel, beyond its magical realist surface, offers a symbolic critique of how displacement in the digital age fractures human identity and transforms the refugee into a posthuman subject. Through close analysis of five central symbols—doors, smartphones, void spaces, the algorithmic gaze, and the refugee body—the study explores how Hamid dramatizes ontological disintegration under conditions of technological mediation and algorithmic control.Using theories from Rosi Braidotti, N. Katherine Hayles, Simone Browne, and Louise Amoore, the research reveals how these symbols function not just aesthetically, but diagnostically, exposing systems that categorize, surveil, and erase the displaced. The paper introduces the concept of algorithmic haunting to describe the refugee as a ghostly data-form, simultaneously visible and forgotten.Methodologically grounded in close reading and interdisciplinary theory, the study positions Exit West as a foundational text in posthuman migration literature. It demonstrates how fiction can illuminate the invisible architectures of digital exile, offering new ways to understand identity, embodiment, and survival in an era of surveillance capitalism